Pengembangan Perangkat Pembelajaran Model PQ4R Media Concept Mapping Terhadap Hasil Belajar Biologi : The Development of Teaching Administrations by Using PQ4R Learning Model Concept Mapping to Learning Outcomes of Biology - Desy Sukma Risalahwati; Makrina Tindangen; Sukartiningsih Sukartiningsih (BIODIK, 2020)
Teachers as an educator play a very important role in the world of education. One way to improve the quality of education in schools is to improve learning qualities in the classroom. In creating these learning activities it is necessary to have an appropriate learning device for the teachers in order to achieve the ultimate goal to be achieved. Based on the reality in the field, not all biology teachers can compile their own learning tools in the discussion of material about the human reproductive system. PQ4R learning model is a learning effort that can foster motivation in students to learn a subject matter and help students to understand and remember the material they are learning and by using concept mapping can be a learning tool to help improve students' memory in learning. This type of research is development research with a combination of research methods (mixed methods), a method that combines quantitative research methods and qualitative methods. In this study, using validation sheets, questionnaires and achievement test.The results of the validation by Prof. Dr. Endang Widi Winarni, M.Pd from Bengkulu University has a valid criterion with a value of 76%. The trial was conducted on students of pharmacy class X-3 at SMK Negeri 17 Samarinda, with the results of paired sample t-test data obtained sig. values 2 tailed at 0,000 which is smaller than 0.05 (0,000 <0.05) which means that Ho is rejected and Ha is accepted, which means there are differences in the average pretest and posttest. Then the effectiveness of the product is tested by comparing the results of the control class posttest and the model class with the results of the Independent sample t-test data obtained sig. values 2 tailed is 0,000 which is smaller than 0.05 (0,000 <0.05) which means that Ho is rejected and Ha is accepted, also means there are differences in the average value of the posttest model class and the posttest control class. From the results of the data analysis, it can be said that the use of the PQ4R learning model and media concept mapping can be applied in learning activities to improve student learning outcomes at school. Keywords: Learning Tools, PQ4R Model, Media Concept Mapping, Biology Learning Outcomes Abstrak. Guru sebagai tenaga pendidik memegang peranan yang sangat penting dalam dunia Pendidikan. Salah satu cara meningkatkan kualitas Pendidikan di sekolah adalah dengan meningkatkan kualitas pembelajaran di dalam kelas. Dalam menciptakan kegiatan pembelajaran tersebut diperlukan adanya perangkat pembelajaran yang sesuai agar dapat mencapai tujuan akhir yang ingin dicapai oleh guru. Berdasarkan kenyataan di lapangan tidak semua guru biologi dapat menyusun sendiri perangkat pembelajaran pada pembahasan materi tentang sistem reproduksi manusia. Model pembelajaran PQ4R merupakan suatu upaya pembelajaran yang dapat menumbuhkan motivasi dalam diri siswa untuk mempelajari suatu materi pelajaran dan membantu siswa untuk memahami dan mengingat materi yang mereka pelajari dan dengan menggunakan concept mapping dapat sebagai sarana belajar untuk membantu meningkatkan daya ingat siswa dalam belajar. Jenis penelitian ini adalah penelitian pengembangan dengan metode penelitian kombinasi (mixed methods) yaitu metode yang mengkombinasikan metode penelitian kuantitatif dan metode kualitatif. Dalam penelitian ini, menggunakan lembar validasi, angket dan tes hasil belajar. Hasil validasi oleh Prof. Dr. Endang Widi Winarni, M.Pd dari Universitas Bengkulu mempunyai kriteria valid dengan nilai 76%. Uji coba dilakukan pada siswa kelas x-3 farmasi SMK Negeri 17 Samarinda dengah hasil uji paired sampel t-test diperoleh data nilai sig. 2 tailed sebesar 0,000 yang lebih kecil dari 0,05 (0,000 < 0,05) yang berarti Ho ditolak dan Ha diterima yang artinya ada perbedaan rata-rata nilai pretest dan posttest. Kemudian diuji efektivitas produk dengan membandingkan hasil posttest kelas kontrol dan kelas model dengan hasil uji Independent sample t-test diperoleh data nilai sig. 2 tailed sebesar 0,000 yang lebih kecil dari 0,05 (0,000 < 0,05) yang berarti Ho ditolak dan Ha diterima yang artinya ada perbedaan rata-rata nilai posttest kelas model dan posttest kelas kontrol. Dari hasil analisis data tersebut dapat dikatakan bahwa penggunaan model pembelajaran PQ4R dan media concept mapping dapat diterapkan dalam kegiatan pembelajaran untuk meningkatkan hasil belajar siswa di sekolah. Kata Kunci: Perangkat Pembelajaran, Model PQ4R, Media Concept Mapping, Hasil Belajar Biologi